"Make way": Pathogen exploitation of membrane traffic. (August 2020) - Noack, Julia; Mukherjee, Shaeri
Abstract: Intracellular pathogens have evolved numerous strategies to manipulate their host cells to survive and replicate in a hostile environment. They often exploit membrane trafficking pathways to enter the cell, establish a replicative niche, avoid degradation and immune response, acquire nutrients and lastly, egress. Recent studies on membrane trafficking exploitation by intracellular pathogens have led to the discovery of novel and fascinating cell biology, including a noncanonical mechanism of ubiquitination and a novel mitophagy receptor. Thus, studying how pathogens target host cell membrane trafficking pathways is not only important for the development of new therapeutics, but also helps understanding fundamental mechanisms of cell biology.